A Pharmacometric Framework for Axitinib Exposure, Efficacy, and Safety in Metastatic Renal Cell Carcinoma Patients. (26th May 2017) - Schindler, E; Amantea, MA; Karlsson, MO; Friberg, LE
Abstract : The relationships between exposure, biomarkers (vascular endothelial growth factor (VEGF), soluble VEGF receptors (sVEGFR)‐1, ‐2, ‐3, and soluble stem cell factor receptor (sKIT)), tumor sum of longest diameters (SLD), diastolic blood pressure (dBP), and overall survival (OS) were investigated in a modeling framework. The dataset included 64 metastatic renal cell carcinoma patients (mRCC) treated with oral axitinib. Biomarker timecourses were described by indirect response (IDR) models where axitinib inhibits sVEGFR‐1, ‐2, and ‐3 production, and VEGF degradation. No effect was identified on sKIT. A tumor model using sVEGFR‐3 dynamics as driver predicted SLD data well. An IDR model, with axitinib exposure stimulating the response, characterized dBP increase. In a time‐to‐event model the SLD timecourse predicted OS better than exposure, biomarker‐ or dBP‐related metrics. This type of framework can be used to relate pharmacokinetics, efficacy, and safety to long‐term clinical outcome in mRCC patients treated with VEGFR inhibitors. (ClinicalTrial.gov identifier NCT00569946.)